ASR, Volume 12, n° 2, 2008 - Full Issue - ssytem, journal (African Sociological Review, 2021)
CONTENTS Editorial ....................................... 1 Articles The Challenges of Studying the African Diasporas Paul Tiyambe Zeleza ............................... 4 Social sciences internationally: The problem of marginalisation and its consequences for the discipline of sociology W. Keim ...................................... 22 Xenophobia and the place of the refugee in the rainbow nation of human rights Ashwin Desai................................... 49 Prendre en compte les échelles: Le mouvement patriotique et la construction de ‘l’autochtone’ en Côte d’Ivoire Karel Arnaut .................................. 69 Address Sociology, Hypocrisy, and Social Order Layi Erinosho ................................. 85 Research Reports Family planning dialogue: Identifying the key determinants of young women’s use and selection of contraception in Namibia Nelago Indongo & Kammila Naidoo ...................... 98 Local perspectives on transnational relations of Cameroonian migrants Michaela Pelican, Peter Tatah & Basile Ndjio............ 117 Adjustment Patterns of and Obstacles against Social Rehabilitation of Sex Workers in Nigeria R. A. Aborisade & A. A. Aderinto ................... 128 ‘I want to be a star’: Doping technology and the incidence of performance-enhancing drugs among actors in Nigeria Charles Emeka Nwadigwe ........................ 144 Measuring Ethnic Identification and Attachment in sub-Saharan Africa Yoku Shaw-Taylor.............................. 155 Debate Can the ‘African household’ be presented meaningfully in large-scale surveys? Marlize Rabe ......................... 167 Book Reviews Anthony J. Bebbington, Samuel Hickey and Diana C. Miltin, eds., Can NGOs Make a Difference? The Challenge of Development Alternatives Reviewed by Kirk D Helliker .......................... 182 Dapo Adelugba and Philip Ogo Ujomu, eds., Rethinking Security in Nigeria: Conceptual Issues in the Quest for Social Order and National Integration Reviewed by Wilson Akpan .................. 184 Isaac Mazonde and Pradip Thomas, Indigenous Knowledge Systems and Intellectual Property in the Twenty-First Century: Perspectives from Southern Africa Reviewed by Rosabelle Boswell ................... 187 Tim Ingold and Jo Lee Vergunst, eds., Ways of walking: Ethnography and practice on foot Reviewed by Detlev Krige ............................ 191